Joint optimal detection of ordering SIC ZF and SIC ZF MAP for V-BLAST/STBC wireless communication systems - Chong, Jin Hui; Khatun, Sabira; Noordin, Nor Kamariah; Mohd Ali, Borhanuddin; Syed Junid, Syed Mansor (2008)
In this paper, we consider a V-BLAST/STBC wireless communication architecture, which integrates Alamouti space-time block codes (STBC) layer with vertical Belllabs layered space-time (V-BLAST) layer, in MIMO wireless communication system with four transmitter and three receiver antennas over Rayleigh flat-fading channel. We propose an algorithm, which combines the algorithm of successive interference cancellation zero-forcing (SIC ZF) and successive interference cancellation zero-forcing with maximum a posteriori probability (SIC ZF MAP). The proposed algorithm (SIC ZF / ZF MAP) reduces the complexity if compared with the algorithm of SIC ZF MAP alone. Simulation results show the symbol error rate performance degradation of the proposed algorithm is small compared to SIC ZF MAP detection.